Trichoderma Species Attract Coptotermes formosanus and Antagonize Termite Pathogen Metarhizium anisopliae - Wen, Chao; Xiong, Hongpeng; Wen, Junbao; Wen, Xiujun; Wang, Cai (Frontiers in Microbiology, 2020)
Although subterranean termites live within soil, little attention has been paid on the potential interaction among subterranean termites and soil microbes. Herein, we conducted different choice tests to investigate aggregation and tunneling behaviors of Coptotermes formosanus Shiraki responding to soil/sand treated with conidia of seven soil fungi, Trichoderma longibrachiatum Rifai, Trichoderma koningii Oud., Trichoderma hamatum (Bon.) Bain., Trichoderma atroviride Karsten, Trichoderma spirale Indira & Kamala, Trichoderma harzianum Rifai, and Trichoderma viride Pers. ex Fries. In aggregation-choice test, soil treated with nearly all Trichoderma species tested (except T. koningii) significantly increased termite aggregation compared with untreated soil. In tunneling-choice tests, termites produced significantly larger tunnels in sand treated with T. longibrachiatum or T. koningii than that in untreated sand. We hypothesized that Trichoderma species could benefit termites by protecting them from infection of the entomopathogenic fungus Metarhizium anisopliae (Metschn) Sorokin, and three Trichoderma species that attracted termites (T. longibrachiatum, T. atroviride, and T. harzianum) were tested. The antagonism tests showed that the three Trichoderma species suppressed growth of M. anisopliae. Also, the median lethal time (LT50) of termites exposed to both Trichoderma species and M. anisopliae was significantly longer than termites exposed to M. anisopliae alone. Interestingly, though significantly fewer termites aggregated in soil treated with M. anisopliae conidia compared with untreated soil, M. anisopliae conidia mixed with T. longibrachiatum or T. harzianum were no longer repellent to termites. Our results showed that the fungi in the genus Trichoderma (1) exerted generally attractive effects on termites, (2) protected termites from the infection of entomopathogenic fungus, and (3) altered pathogen-avoiding behaviors of termites. Future studies will be required to understand the mechanisms underlying these newly discovered effects.